Exercícios físicos para pacientes com aneurismas fusiformes e assintomáticos de aorta abdominal: revisão sistemática e metanálise - Oliveira, Ricardo De Avila [UNIFESP] (2019)
Background: 87.7% of all aortic aneurysms are small and not referred to surgery. Furthermore, despite rupture risks with diameter increments, mortality is commonly related to cardiovascular causes including myocardium infarction and stroke. This way, there is a glaring need for changing cardiovascular risks for these patients, to prolong life, improve quality of life, and reduce surgical complications. Physical exercises are particularly relevant to reach those goals. Therefore, we conducted a systematic review to assess effectiveness and safety of physical exercises comparing to usual care for fusiform and asymptomatic abdominal aortic aneurysm patients. Methods: A systematic review following Cochrane systematic review handbook was conducted using the mesh terms “aortic aneurysm” and “exercise” in Medline, Embase, central, lilacs, PeDRO, cinahl, clinicaltrials.gov, who – ICTRP, and opengray. Two independent researchers collected, extracted, assessed the quality of studies, and made data synthesis. Results: 1189 references were collected and selected. Eight studies from clinical trials were included. There were no death or aortic rupture related to exercises as well as there was no reduction in aneurysm growth rate. Six weeks pre-operative exercises reduced severe complications (RR: 0.54 [0.31, 0.93] CI 95%) and subgroup analysis showed a predilection to reduce renal and cardiac complications. Indeed, it decreased intensive-care unit stay (MD: -1.00 [-1.26, -0.74] CI 95%). Pre- and post-operative forward walking reduced hospital stay (MD: -0.69 [-1.24, -0.14] CI 95%). Quatity of life was evaluated in one study that related no improvements for small aneurysm patients during surveillance. Conclusions: According to a very low level of evidence, there was no reduction in aneurysm growth rates, patients referred to surgery, and mortality or rupture. However, there was a reduction in post-operative complications and intensive care unit stay. Pre- and post-operative exercises reduced hospital stay.